Mental Health Literacy among Students of Gujranwala Division of Punjab - Yasir Sadiq, Kanwal Khalid, Zain Imtiaz, Komal Mushtaq, Zarwa Manan, Amtul Hafeez, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Treatment of either physical or mental illnesses is not as effective if the knowledge and awareness of the patient is inadequate. Study design: Descriptive study. Methodology: A total number of 240 students through convenient sampling who responded to the questionnaire. The ethical approval was obtained from review ethical committee, after completing and submitting the research proposal. The research instrument for data collection was, “structured questionnaire” developed by using 2 scales, the mental health literacy scale (MHLS) and modified scale. Data was analyzed by SPSS version 23. Chi-square test was applied for categorical variables to find the differences in knowledge and practices by dental professionals with p-value ≤0.05 as significant. Results: Almost 86.7% of students were able to identify major depressive disorder.8.3% thought such disorders are punishment by God, 38.3% of students considered mental illness as inherited trait. According to 47.5% treatment of mental illness caused addiction, 37.1% were unsure and 15.4% disagreed. Practical Implication: This study helped researchers in exploring role of multiple factors in changing mental health literacy and how it can help in reducing those barriers and promoting mental health literacy in students. This also added to local literature regarding mental health. Conclusion: It was concluded that mental illness needs recognition and awareness campaigns for mental health literacy needs to be conducted. Keywords: Mental Health, Knowledge, Awareness, Attitude and Individual Performance.